DELONE AND EPHRAIM R. MCLEAN METHOD TO MEASURE THE SUCCESS OF INFORMATION SYSTEMS (IS) IN PESHAWAR. - Ali, Umar (Asia Information System Journal, 2023)
The DeLone and McLean Model of Information Systems Success is a framework developed by William H. DeLone and Ephraim R. McLean to measure the success of information systems (IS) in Pakistan and India. The model identifies six interrelated dimensions of IS success: System Quality, Information Quality, Use, User Satisfaction, Individual Impact, and Organizational Impact. The original model (1992) identified six dimensions of IS success: System Quality, Information Quality, Use, User Satisfaction, Individual Impact, and Organizational Impact. The study aims to address the problem phenomena in information systems, such as user dissatisfaction, system quality, and service quality, which can hinder the overall success of IS. Perceived ease of use and service quality are identified as significant factors impacting user satisfaction and net benefits of academic information systems. Addressing these problems is crucial for improving user experience and system functionality in higher education institutions. The model was first introduced in 1992 and updated in 2003 to incorporate feedback and changes in the field over ten years.